Demographic variation in active consumer behaviour: On-line search for retail broadband services. Issue 7 (July 2020) - Carthy, Philip; Lunn, Peter D.; Lyons, Sean
Abstract: Consumers who actively search for better broadband deals may benefit from lower prices or improved service quality compared to those who do not. If, however, consumers differ in their propensity to engage with the market and actively search, these potential benefits may not accrue equally. This paper investigates differences in consumer search activity for telecommunications services across small geographic areas. We exploit rich and novel data from a commercial price comparison site to explore the dispersion of consumer search in the Irish retail broadband market, while controlling for supply-side variations. By linking geo-coded searches to census data on small area socio-economic characteristics, we identify the areas where most search originates and can thus characterise the socio-economic groups to whom the benefits of search are most likely to accrue. We find evidence that areas populated by many highly educated, married people, commuters, mortgage holders, and retirees are among the most active in search. In contrast, those areas in which many older people, farmers, low-skilled workers and students reside give rise to significantly fewer consumer searches. Abstract : Broadband services; Consumer search behaviour; Socio-economic effects; Ireland, behavioural economics; Microeconomics; Technology management; Consumer attitude; Consumer psychology, psychology, business, economics